Archetypal Analysis of Amy Dunne in Gone Girl Film - Syaputri, Yoshsyta Eka Ahdiyat Virzinia; Kuncara, Singgih Daru; Dewi M., Jonathan Irene Sartika (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This research analyzes the Gone Girl film protagonist character which is Amy Dunne. The purpose of this research is to find the archetypes representation of Amy Dunne using Jung's theory. The data were generated from the actions and dialogues from the film script and Amy's representation of the archetypes. There are four kinds of archetypes in order to acknowledge the representation of archetypes. They are ‘persona’, ‘shadow’, ‘anima and animus’, and ‘self’. With the archetypes and characterization assistance in analyzing the archetypes represented by the main characters, it is found that Amy Dunne shows archetypes from her. The archetype itself has four types, and Amy shows four types which are persona, shadow, animus, and self. While analyzing this film, with the help film’s characterization method the researcher found that the ‘shadow’ dominates Amy Dunne’s character. It can be stated that the shadow was the archetype that most accurately depicted Amy's personality. the researcher hopes that this research will be useful for readers about those archetypes that can occur in everyday life and that people can show different personalities to their surroundings.